International Logistics Performance Based on the DEA Analysis - Sternad, Marjan; Skrucany, Tomas; Jereb, Borut (Communications - Scientific letters of the University of Zilina, 2018)
Logistics is a very important service, which can influence the international trade. However, the rates in the development of international activities vary by country. In developing countries, the share of the logistics services is increasing, while the share of manufacturing activities, especially those with the lower added value, is declining due to the relocation of production to other countries. In order to achieve competitive advantages in the logistics sector, the development of logistics services with the higher added value is required. The effectiveness of logistics processes is very important for international competitiveness. In the paper, is presented the literature review on logistics performance. After presenting relevant research, the effectiveness of logistics is compared using the logistics performance index based on the Data Envelopment Analysis (DEA). The DEA analysis is a benchmarking technique which is useful for a multi-criteria comparison. Values of the international logistics performance index for 2016, for selected European countries, were used for the input and output variables of the DEA model. European countries rank high in the international comparison of the logistics performance index. In the paper, it was found out that the compared countries are competitive in international business, but not all the countries are considered as efficient. Germany achieves the highest points in the international comparison of the LPI but, does not achieve efficiency. We also found out that Austria, Serbia, Russian Federation and Bosnia and Herzegovina were efficient, while other compared countries did not.